Ligand-assisted olefin-switched divergent oxidative Heck cascade with molecular oxygen enabled by self-assembled imines. Issue 9 (4th April 2023) - Liu, Bairong; Rao, Jianhang; Liu, Weibing; Gao, Yang; Huo, Yanping; Chen, Qian; Li, Xianwei
Abstract : Divergent oxidative Heck reaction has proven to be reliable for the rapid construction of molecular complexity, while olefins switched the outcome that remained underexplored. Abstract : Divergent oxidative Heck reaction has proven to be reliable for the rapid construction of molecular complexity, while olefins switched the outcome that remained underexplored. Herein, olefins tuned the divergent oxidative Heck reaction with O2, enabled by self-assembled imines, which was achieved with site selectivity and stereoselectivity. The compatiblity of strongly coordinating pyridines and quinolines enabled the concise delivery of a selective serotonin 4 receptor ligand, topotecan, and irinotecan analogues.